2010
DOI: 10.1111/j.1476-5381.2010.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacology of chemically distinct NADPH oxidase inhibitors

Abstract: BACKGROUND AND PURPOSE Oxidative stress [i.e. increased levels of reactive oxygen species (ROS)] has been suggested as a pathomechanism of different diseases, although the disease‐relevant sources of ROS remain to be identified. One of these sources may be NADPH oxidases. However, due to increasing concerns about the specificity of the compounds commonly used as NADPH oxidase inhibitors, data obtained with these compounds may have to be re‐interpreted. EXPERIMENTAL APPROACH We compared the pharmacological prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
191
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(201 citation statements)
references
References 48 publications
4
191
2
1
Order By: Relevance
“…Pretreatment of platelets with diphenylene iodonium (DPI), an inhibitor of various sources of oxygen radical including NADPH oxidase, 31 resulted in less binding of opsonized platelets to CRP compared with untreated opsonized platelets ( Figure 4E). A similar reduction in binding of platelets to CRP was observed in the presence with Rotenone, a compound more specifically inhibiting the mitochondrial electron transport chain ( Figure 4F).…”
Section: Platelet Oxidation Exposes Crp Ligandsmentioning
confidence: 99%
“…Pretreatment of platelets with diphenylene iodonium (DPI), an inhibitor of various sources of oxygen radical including NADPH oxidase, 31 resulted in less binding of opsonized platelets to CRP compared with untreated opsonized platelets ( Figure 4E). A similar reduction in binding of platelets to CRP was observed in the presence with Rotenone, a compound more specifically inhibiting the mitochondrial electron transport chain ( Figure 4F).…”
Section: Platelet Oxidation Exposes Crp Ligandsmentioning
confidence: 99%
“…Moreover, Nox has been identified as the major source for NADPH-dependent production of superoxide anion in cardiac tissue (Nediani et al 2007). As apocynin, the most used Nox inhibitor, interferes with H2O2 detection with Amplex Red in cell-free systems (Heumuller et al 2008) and can behave itself as an antioxidant acting as a scavenger of reaction products of hydrogen peroxide (Wind et al 2010), we have experimentally assessed that apocynin affords a large inhibition of the coupled NADPH oxidase activity in our cardiac homogenates of doxorubicin-treated rats (day 3 post-injection). Our results showed that 250 and 500 μM apocynin inhibited 75±5% and >90%, respectively, of the total NADPH oxidase activity, which was 1.5±0.1 nmoles/min/mg of protein measured as indicated in the Materials and Methods section (average of data obtained with three different homogenates).…”
Section: C Of Supplementary Data)mentioning
confidence: 99%
“…Nrf2/HO-1) [19] or source specific inhibitors (e.g. for different Nox isoforms) [20], or even repair the resulting oxidative damage (e.g. activators and stimulators of oxidized soluble guanylyl cyclase) thus leaving important cellular redox signaling mechanisms intact [13,21].…”
Section: Reactive Oxygen and Nitrogen Species Formation Redox Biologmentioning
confidence: 99%